MEL BOCHNER AND ALIGHIERO BOETTI: VERBA VOLANT SCRIPTA MANENT. - ROONEY, KARA L. (Brooklyn Rail, 2016)
The article reviews an exhibition "Verba Volant Scripta Manent" running at Totah Gallery in New York City from February 25, 2016 featuring textile works by artists Mel Bochner and Alighiero Boetti.